PENGARUH MODEL EXPERIENTIAL LEARNING TERHADAP HASIL BELAJAR SISWA SD NEGERI 06 PONTIANAK KOTA - Maisyaroh, Umi; Sabri, Tahmid; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine wheather there is an effect or not and how much the effect has on experiential learning model on student’s learning outcomes in Natural Science for IV grade SD Negeri 06 Pontianak Kota. The used method is an experiment in the form of quasi-experimental design with the kind of nonequivalent control group design. The population is all students of IV grade. The sample consisted of IV B grade as an experimental class and IV A grade as a control class selected by purposive sampling technique. Data collection technique that is used is measurement with data collection tool in written test in the form of multiple choices. Analysis of post-test results using the polled variance t-test shows the value of t_count (3.312) > t_table (2.0141). It means, there are significant differences between student learning outcomes of the experimental class and the control class, so it can be concluded that there is an effect of the experiential learning model on student’s learning outcomes. From the calculation of the effect size obtained 0.699 which means learning with experiential learning model gives a moderate effect on student’s learning outcomes in Natural Science for IV grade SD Negeri 06 Pontianak Kota. Keywords: Experiential Learning Model, Student’s Learning Outcomes